Heat‐Triggered Crystallization of Liquid Crystalline Macrocycles Allowing for Conductance Switching through Hysteretic Thermal Phase Transitions. Issue 1 (26th November 2018) - Muraoka, Takahiro; Shima, Tatsuya; Kajitani, Takashi; Hoshino, Norihisa; Morvan, Estelle; Grélard, Axelle; Dufourc, Erick J.; Fukushima, Takanori; Akutagawa, Tomoyuki; Nabeya, Kota; Kinbara, Kazushi
Abstract: A polymesomorphic thermal phase‐transition of a macrocyclic amphiphile consisting of aromatic groups and oligoethylene glycol (OEG) chains is reported. The macrocyclic amphiphile exists in a highly‐ordered liquid crystal (LC) phase at room temperature. Upon heating, this macrocycle shows phase‐transition from columnar‐lamellar to nematic LC phases followed by crystallization before melting. Spectroscopic studies suggest that the thermally induced crystallization is triggered by a conformational change at the OEG chains. Interestingly, while the macrocycle returns to the columnar‐lamellar phase after cooling from the isotropic liquid, it retains the crystallinity after cooling from the thermally‐induced crystal. Thanks to this bistability, conductance switching was successfully demonstrated. A different macrocyclic amphiphile also shows an analogous phase‐transition behavior, suggesting that this molecular design is universal for developing switchable and memorizable materials, by means of hysteretic phase‐transition processes. Abstract : Going through phases : A macrocyclic amphiphile with a multiblock structure shows a polymesomorphic thermal phase‐transition from a highly‐ordered liquid crystalline phase to a nematic phase and crystallization before melting upon heating. The amphiphile retains the crystallinity after cooling from the thermally‐induced crystal, while cooling from the isotropic liquid resulted in the return to the liquid crystalline phase. This hysteretic bistability enables conductance switching by the thermal process.